KEBIJAKAN HUKUM PIDANA KEBIRI TERHADAP PELAKU KEKERASAN SEKSUAL PADA ANAK DIKAITKAN DENGAN SISTEM PEMIDANAAN - Isfan Santia Budi; Emilda Firdaus; Mukhlis R (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
One form of protection for children to anticipate the increase in violence against children, the Government issued Perpu Number 1 of 2016 which was ratified into Law Number 17 of 2016 concerning the stipulation of Perpu Number 1 of 2016 concerning the second amendment to Law Number 23 of 2002 concerning Child protection. The regulation provides assistance on the strengthening of sexual crimes, especially children. In the Perpu criminal assistance and action. The Perpu states that the perpetrator who commits a criminal act can be given action in the form of chemical castration with rehabilitation which will be reviewed directly through the criminal system.This study aims to explain the chemical castration criminal law policy that applies in Indonesia in relation to the purpose of punishment. This research is a normative juridical research that conceptualizes law as a norm including values, positive law and court decisions. Legal materials are collected by means of document studies and library research, namely by combining primary, secondary and tertiary legal materials related to chemical castration criminal law policies in terms of criminal law and criminal law policy theory.The conclusions that can be obtained from the research results are First, the criminal law policy in Law Number 1 of 2016 concerning the second amendment to Law Number 23 of 2002 concerning Child Protection views chemical castration against perpetrators of sexual violence in children currently considers chemical castration as an act that is separate from rehabilitation efforts does not look at chemical castration in the context of the perpetrator's rehabilitation. Second, the ideal castrated criminal law policy against perpetrators of sexual violence against children is associated with the criminal system, namely paying attention to the criminal system itself so that the criminal law policy process is mutually correlated, because in the criminal system there is such a thing as a relative theory or objective theory.Keywords: Policy, Criminal Law, Sexual Violence, Chemical Castration, Criminalization.